The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages Q.— Who is responsible for ventilation in factories? A.— The manager is primarily responsible for everything in the factory — for all health and safety measures and at present he must remain so. Q.— Would the doctor advise with regard to Factory Welfare Officers that they should be under the jurisdiction of the Ministry of Labour rather than being directly employed by the factory owner? A.— Yes. It would be better. This applies to nurses, too. Q.— Is it possible to get extra rations of tea and eggs for miners? A.— Extra rations should certainly be provided for miners. The heavy work of the miner unquestionably calls for a very high calorific intake of food. I question very much whether miners are getting this in many cases. The canteen facilities for miners are much lower than for other workers. VITAL HEALTH STATISTICS (England and Wales Maternal Mortality Infantile Mortality T. B. Mortality Year No. Rate per 1000 Tot. Bths. No. Rate per 1000 Live Bths. No. Rate per 1000 of Pop't'n. 1940 1640 2.60 33,892 56 28,144 .679 1941 1678 2.76 34,550 59 28,670 .692 1942 1673 2.47 32,257 49 25,547 .616 LOCAL HEALTH STATISTICS Place. Maternal Mortality Rate per 1000 Infantile Mortality Rate per 1000 T. B Mortality Rate per 1000 Gateshead (1941) 4.78 90 1.44 Jarrow (1942) 8.05 74 1.04 Tynemouth (1941) 3.32 67 1.16 Newcastle (1941) 2.82 76 0.98 Blyth (1941) 7.8 89 — Consett (1942) — 59 — Co. Durham (1941) 3.57 54 0.61 Northumberland (1939) 3.15 55 0.52 14 15X/2/103/295